Implementasi Penataan Ruang Kelas Dalam Membentuk Interaksi Siswa Pada Proses Pembelajaran Di Kelas - Apriani, Kherina; Badrusalam, Ujang; Rosadi, Adi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
This study is motivated by the low level of active student participation in the classroom, as reflected in 2025 data: only 20% of students asked questions, 36% answered, 28% participated in discussions, and 12% expressed opinions during the learning process. This condition is caused by a rigid classroom atmosphere, limited space for movement, and a classroom layout that does not support peer interaction. This study aims to explore the planning, implementation, and evaluation of classroom layout, as well as its impact on student interaction. A qualitative approach with a case study method was employed, categorized as field research. The research subjects included the classroom teacher, principal, administrative staff, and students at MI BPPI Citiis Sukabumi. Data were collected through observation, interviews, and documentation. The data analysis process involved data reduction, presentation, and conclusion drawing. The results reveal that: 1) classroom planning considered visual comfort, viewing distance, and access to learning media; 2) the implementation process included flexible seating arrangements, use of visual media, and attention to cleanliness; 3) evaluations were conducted informally and regularly by the teacher; and 4) the impact included increased student interaction, willingness to ask questions, and stronger teacher-student relationships. The study concludes that appropriate classroom layout contributes to more active and meaningful learning interactions.